2021
DOI: 10.3390/molecules27010166
|View full text |Cite
|
Sign up to set email alerts
|

Abietane Diterpenes of the Genus Plectranthus sensu lato

Abstract: Plectranthus (Lamiaceae), which—according to the latest systematic revision—includes three separate genera (Coleus, Plectranthus sensu stricto, and Equilabium), is a genus widely used in traditional medicine—mainly in the treatment of various ailments of the digestive tract, respiratory tract, and skin. Many species of Plectranthus s.l. have been shown to produce phenolic compounds and terpenes. Diterpenes, especially those of the abietane class, are the most studied group of secondary metabolites found in Ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 124 publications
(128 reference statements)
0
19
0
Order By: Relevance
“…Among all phytochemical classes, diterpenes are the most prominent biologically active group of secondary metabolites present in this genus, whose presence is considered as a chemotaxonomic marker [38]. In particular, abietane diterpenes have attracted attention regarding their biological activities, namely because of their antiproliferative, antitumoral, and/or cytotoxic potential [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Among all phytochemical classes, diterpenes are the most prominent biologically active group of secondary metabolites present in this genus, whose presence is considered as a chemotaxonomic marker [38]. In particular, abietane diterpenes have attracted attention regarding their biological activities, namely because of their antiproliferative, antitumoral, and/or cytotoxic potential [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The last compound 7α-formyloxy-6β-hydroxyroyleanone ( 7) is newly isolated from C. forsteri. It was previously found in other Coleus species (Gáborová et al, 2022). However, bioactivities of compound (7) were barely studied.…”
Section: Discussionmentioning
confidence: 96%
“…Plectranthus sensu lato is a large and widespread genus with an important range of ethnobotanical uses including medicinal purposes ( Lukhoba et al, 2006 ; Rice et al, 2011 ). Phytochemical studies have shown that this genus, including Coleus species, is a rich source of diterpenes exerting promising biological activities with abietane diterpenes as the most abundant group ( Abdel-Mogib et al, 2002 ; Gáborová et al, 2022 ). Interestingly, commercial extract of C. amboinicus was shown to inhibit maturation and release of inflammatory cytokine IL-1β through inhibition of nuclear factor NF-kB translocation ( Leu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations